Evaluation of Efficacy of Collagen-Calcium Alginate Protectants on Chronic Wound Healing in Horses - Hussin, Khaled. M. A.; W, Asma Saleh; Hamad, Rehab; Saleh, Marwan (Al-Mukhtar Journal of Sciences, 2021)
This study aimed to evaluate the efficacy of collagen-calcium alginate as an accelerator of wound healing in a clinical case of ten horses attended at the University Veterinary Hospital (UVH) at Omar Al-Mukhtar University, having non-healing chronic wounds. The pattern of wound healing was evaluated both clinically and by planimetry. All cases showed healing progress after the application of the collagen-calcium alginate film. The study results suggested that collagen-calcium alginate film can be a better wound healing biomaterial in horses. It can be used as a less expensive skin substitute in order to stimulate and promote wound healing in animals especially in the case of chronic non-healing wounds.